Participation, representation, and shared experiences of women scholars in biological anthropology. (30th January 2018) - Turner, Trudy R.; Bernstein, Robin M.; Taylor, Andrea B.; Asangba, Abigail; Bekelman, Traci; Cramer, Jennifer Danzy; Elton, Sarah; Harvati, Katerina; Williams‐Hatala, Erin Marie; Kauffman, Laurie; Middleton, Emily; Richtsmeier, Joan; et al.
Abstract: American Association of Physical Anthropologists (AAPA) membership surveys from 1996 and 1998 revealed significant gender disparities in academic status. A 2014 follow‐up survey showed that gender equality had improved, particularly with respect to the number of women in tenure‐stream positions. However, although women comprised 70% of AAPA membership at that time, the percentage of women full professors remained low. Here, we continue to consider the status of women in biological anthropology by examining the representation of women through a quantitative analysis of their participation in annual meetings of the AAPA during the past 20 years. We also review the programmatic goals of the AAPA Committee on Diversity Women's Initiative (COD‐WIN) and provide survey results of women who participated in COD‐WIN professional development workshops. Finally, we examine the diversity of women's career paths through the personal narratives of 14 women biological anthropologists spanning all ranks from graduate student to Professor Emeritus. We find that over the past 20 years, the percentage of women first authors of invited symposia talks has increased, particularly in the sub‐disciplines of bioarchaeology, genetics, and paleoanthropology. The percentage of women first authors on contributed talks and posters has also increased. However, these observed increases are still lower than expected given the percentage of graduate student women and women at the rank of assistant and associate professor. The personal narratives highlight first‐hand the impact of mentoring on career trajectory, the challenges of achieving work‐life satisfaction, and resilience in the face of the unexpected. We end with some suggestions for how to continue to improve equality and equity for women in biological anthropology.